Linking the Questions: Judicial Supremacy As a Matter of Constitutional Interpretation - Tabatha Abu El-Haj (Washington University Law Review, 2012)
This Article explains that what has been missing from the debate between advocates of popular constitutionalism and defenders of judicial supremacy is any account of the practice of constitutional interpretation. Without a clear sense of what constitutional interpretation involves, one cannot assess the prevailing assumption that the Supreme Court is uniquely positioned to interpret the Constitution or explore an expertise-based justification for its claim to finality. This Article, therefore, revisits the debate about judicial supremacy by starting, not with history or politics, but with constitutional interpretation itself. Having explored the conventions of argument that constitute the practice of constitutional interpretation, this Article concludes that the Supreme Court can claim expertise with respect to determining constitutional meaning, but that its expertise has limits. It proceeds to explore whether and how this insight might be translated into limits to judicial supremacy. Toward that end, this Article develops a framework for assessing when the work of constitutional interpretation should be shared between the Supreme Court, the other branches of government, and the public itself. Finally, it uses the Court's doctrine with respect to race-conscious legislative districting to illustrate how the proposed framework might work.
Keywords: Constitutional interpretation; U.S. Supreme Court; Judicial supremacy; Voting Rights Act